Peran Manusia Dalam Mempertahankan Ketersediaan Sumber Daya Alam Melalui Etika Lingkungan - Samsul Hadi; Taslim Sjah; Muhammad Sarjan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
The environmental conditions significantly influence human daily life, especially their reliance on natural resources such as land, water, and air. However, environmental degradation in Indonesia is increasing due to a lack of attention to environmental ethics, driven by materialistic views and economic incentives resulting in a global ecological crisis. The environment encompasses everything that affects the survival of humans and other creatures. Environmental ethics are crucial to maintaining the balance of nature. There are three theoretical perspectives on environmental ethics: anthropocentrism, biocentrism, and ecocentrism. The principles of environmental ethics include collective responsibility, care for nature, non-harm to other living beings, simple living, justice in resource management, democracy in environmental policy-making, and moral integrity. Implementing environmental ethics involves a friendly attitude towards the environment in every aspect of life. Human behavior towards the environment should reflect an awareness of collective responsibility for preserving nature, even though technological advancements tend to harm the environment. Concrete actions from all parties are needed to preserve and restore the environment.